2013
DOI: 10.1007/s40279-013-0042-0
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Phosphate as an Ergogenic Aid

Abstract: Legal nutritional ergogenic aids can offer athletes an additional avenue to enhance their performance beyond what they can achieve through training. Consequently, the investigation of new nutritional ergogenic aids is constantly being undertaken. One emerging nutritional supplement that has shown some positive benefits for sporting performance is sodium phosphate. For ergogenic purposes, sodium phosphate is supplemented orally in capsule form, at a dose of 3-5 g/day for a period of between 3 and 6 days. A numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
1
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 52 publications
0
31
1
5
Order By: Relevance
“…CP is an endogenous, bioactive molecule that is mainly synthesized in the kidney. It plays dual roles in the storage and transfer of ATP in energy metabolism [7], and thus provides energy for the body. CP is rapidly decomposed to provide energy in the presence of oxygen and suppresses the generation of multiple acidic toxic substances, maintaining a stable intracellular environment and promoting cellular repair [33].…”
Section: Discussionmentioning
confidence: 99%
“…CP is an endogenous, bioactive molecule that is mainly synthesized in the kidney. It plays dual roles in the storage and transfer of ATP in energy metabolism [7], and thus provides energy for the body. CP is rapidly decomposed to provide energy in the presence of oxygen and suppresses the generation of multiple acidic toxic substances, maintaining a stable intracellular environment and promoting cellular repair [33].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the mechanisms proposed to contribute to the benefit of sodium phosphate supplementation for exercise performance relate to all energy systems as discussed below (and reviewed in Buck, Wallman, Dawson, & Guelfi, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Another factor that may have improved aerobic energy contribution during these later repeated-sprint ability sets is enhanced RBC 2,3-DPG concentration (Buck, Wallman, Dawson, & Guelfi, 2013;Czuba et al, 2009). To date, a number of studies have reported improved exercise capacity ( _ VO 2max ) following sodium phosphate supplementation associated with an increase in 2,3-DPG concentration (Cade et al, 1984;Czuba et al, 2009;Stewart et al, 1990).…”
Section: Effects Of Sodium Phosphate and Caffeine On Repeated-sprint mentioning
confidence: 99%
“…Another mechanism associated with sodium phosphate loading that may have improved aerobic metabolism during the latter repeated-sprint ability sets is improved myocardial efficiency, which is proposed to result in greater stroke volume leading to greater oxygenation of the exercising muscles (Buck et al, 2013). Interestingly, maximal heart rate associated with improved _ VO 2max (Czuba et al, 2009) and 40-km cycle time-trial performance (Kreider et al, 1992) has been found to be both significantly lower (Czuba et al, 2009) and higher (Kreider et al, 1992) after sodium phosphate loading compared with placebo.…”
Section: Effects Of Sodium Phosphate and Caffeine On Repeated-sprint mentioning
confidence: 99%